Preventive health practices and colorectal cancer screening in women veterans - Emma Schnittka; Promila Banerjee; Hepsi Kalapala (Academia Global and Public Health, 2026)
Introduction: Colorectal cancer (CRC) is the fourth-leading cause of cancer-related mortality among U.S. women and the second-leading cause among women younger than 50 years. Although screening reduces CRC incidence and mortality, adherence remains below national targets. This study evaluated associations between CRC screening compliance and other preventive health practices among women veterans. Materials and methods: A retrospective cross-sectional analysis was conducted at the Edward Hines Jr. Veterans Affairs (VA) Hospital Women’s Health Clinic. Data obtained from the VA Electronic Quality Management system included age, ethnicity, influenza vaccination status, and breast, cervical, and CRC screening status. Associations between CRC screening adherence and breast cancer screening, cervical cancer screening, and influenza vaccination were summarized using unadjusted odds ratios (ORs) with 95% confidence intervals (CIs) calculated by Fisher’s exact test. Univariable logistic regression was used to evaluate the association between age and CRC screening compliance. Results: 724 patients met VA electronic technical measure (eTM) eligibility criteria for the CRC screening assessment, and 65.5% were screening-compliant. CRC screening compliance was significantly associated with breast cancer screening (OR 3.76, 95% CI 2.32–6.10), cervical cancer screening (OR 1.96, 95% CI 1.08–3.51), and influenza vaccination (OR 1.92, 95% CI 1.38–2.68) (all p < 0.05). Age was not significantly associated with CRC screening compliance. Conclusions: Among women veterans, adherence to other preventive health practices was associated with increased CRC screening compliance. Despite study limitations, including retrospective design and single-center data, findings highlight opportunities to leverage existing preventive healthcare encounters to improve CRC screening uptake.